A study of serum psedocholinesterase levels following diazinon poisoning in relation to liver function-prognostic and therapeutic value - Swarnalatha, K.; Rao, B. Surya Prakasa; Sonia, S. Sharon (International Journal of Basic & Clinical Pharmacology, 2017)
Background: To study serum pseudo-cholinesterase (PChE) levels as an index of liver injury in individuals with diazinon poisoning with or without alcoholism. It gives the knowledge of the therapeutic efficacy and severity of liver dysfunction. Methods: Blood samples were taken from normal male adults as control and PChE is estimated. Blood samples were taken from diazinon poisoning patients from local hospitals on the 1st day and on 5th day for pseudocholinesterase estimation. Another group of blood samples were taken on the 1st day and on the 5th day from diazinon poisoning patients with history of alcoholism serum PChE is estimated. Results: Serum PChE was estimated among the normal healthy male adults as the normal value of enzyme for the various levels for comparison. Among 30 normal adults, the control value of PChE ranged between 125 and 321 µmol/ml with 212 as the mean. Following the treatment with atropine, PAM and blood transfusion, blood samples were estimated by 5th day among patients with diazinon. Their mean value was found to be 200 µmol/ml. Among individuals with alcohol and diazinon poisoning, following the treatment, the serum PChE levels were raised comparatively on 1st day. The value is 100 µmol/ml. Conclusions: In diazinon poisoning without alcoholism, the prognostic and therapeutic efficacy of the drugs is better unlike in alcoholics. Hence a scope of necessitating the hepatoprotective measures is of consideration in the organophosphorous poisoning cases.